Bone-targeted polymeric nanoparticles as alendronate carriers for potential osteoporosis treatment. (June 2022) - Jing, Chunlan; Chen, Shenmao; Bhatia, Sehajdev Singh; Li, Bowen; Liang, Hongze; Liu, Chaozong; Liang, Zhenjiang; Liu, Junying; Li, Haiyan; Liu, Ziyu; Tan, Hui; Zhao, Lingling
Abstract: Bone-targeted polymeric nanoparticles for alendronate delivery based on Poly (lactic-co-glycolic acid) conjugated chitosan (CS-PLGA) and alendronate conjugated PLGA (Alen-PLGA) are fabricated and their superior performances are evaluated. The nanoparticles exhibited sustained Alen release without obvious burst release and good cytocompatibility against MC3T3 cells. Alen-modified nanoparticles demonstrated a high affinity to hydroxyapatite, which is the main mineral component of bone, indicating their feasibility for bone-targeted delivery. In addition, unlike nanoparticles without Alen, Alen-modified nanoparticles were preferentially taken up by MC3T3 cells, compared to HDF cells, revealing their specific uptake for osteoblast-like cells. Thus, the Alen-modified nanoparticles can potentially be developed as bone-targeted carriers for osteoporosis treatment. Highlights: Alendronate-modified polymeric nanoparticles were prepared for bone-targeted delivery of alendronate. The nanoparticles showed sustained Alen release without obvious burst release and good cytocompatibility against MC3T3 cells. The nanoparticles demonstrated a high affinity to hydroxyapatite. The nanoparticles revealed specific uptake for osteoblast-like cells.